Inhibition of extracellular signal-regulated kinase pathway suppresses tracheal stenosis in a novel mouse model. - Akari Kimura (Public Library of Science (PLoS), 2021)
Tracheal stenosis is a refractory and recurrent disease induced by excessive cell proliferation within the restricted tracheal space. We investigated the role of extracellular signal-regulated kinase (ERK), which mediates a broad range of intracellular signal transduction processes in tracheal stenosis and the therapeutic effect of the MEK inhibitor which is the upstream kinase of ERK. We histologically analyzed cauterized tracheas to evaluate stenosis using a tracheal stenosis mouse model. Using Western blot, we analyzed the phosphorylation rate of ERK1/2 after cauterization with or without MEK inhibitor. MEK inhibitor was intraperitoneally injected 30 min prior to cauterization (single treatment) or 30 min prior to and 24, 48, 72, and 96 hours after cauterization (daily treatment). We compared the stenosis of non-inhibitor treatment, single treatment, and daily treatment group. We successfully established a novel mouse model of tracheal stenosis. The cauterized trachea increased the rate of stenosis compared with the normal control trachea. The phosphorylation rate of ERK1 and ERK2 was significantly increased at 5 min after the cauterization compared with the normal controls. After 5 min, the rates decreased over time. The daily treatment group had suppressed stenosis compared with the non-inhibitor treatment group. p-ERK1/2 activation after cauterization could play an important role in the tracheal wound healing process. Consecutive inhibition of ERK phosphorylation is a potentially useful therapeutic strategy for tracheal stenosis.